Sustainable application of grinding wheel waste as abrasive for abrasive water jet machining process. (10th July 2020) - Sabarinathan, P.; Annamalai, V.E.; Rajkumar, K.
Abstract: In grinding operation, stub portion of the grinding wheel is unused and dumped as waste. The present research work deals with recycling and reusing of alumina grinding wheel waste as abrasive grain in abrasive water jet machining process (AWJM). Recycled alumina abrasive grains were recovered by mechanical crushing method. Abrasive particle characterization such as particle morphology and shape factor for recycled alumina grain were done by Scanning Electron Microscopy (SEM), and elemental composition was also measured using Energy Dispersive Spectroscopy (EDX) analysis. Shape factor of recycled alumina was 0.92, indicating that angularity with many sharp edges are present in periphery of the grain. Effectiveness and performance of the recycled alumina were compared with garnet abrasive grain in abrasive water jet machining process. Constant factor experimental study has been done on marble and aluminium standard workpiece materials. Performance indicators for the abrasive grains namely, material removal, kerf width, cutting depth and cutting time were measured. Material removal efficiency of recycled alumina was 43% higher for aluminium and 63%higher for marble machining. Cutting depth efficiency, indicated by deeper cutting ability of recycled alumina abrasive, was higher for standard workpiece materials. The requirement of short cutting time was met by recycled alumina abrasive for both the aluminium and marble machining under constant cutting parameter conditions. Material removal of marble with recycled alumina grain reveals larger lateral cracks indicative of significant material removal as required by granite and marble cutting industry. As a result of substantial material removal by recycled alumina, the machined surfaces were showing a higher surface roughness. From the results, it can be recommended that recycled alumina is most suited for rough cutting operation of marble and granite cutting industries. Graphical abstract: Image 1 Highlights: Recycling of alumina grinding wheel rejects. Recycled alumina possesses angularity and sharp edges. Recycled alumina removes more material. Recycled alumina shows deeper cutting than garnet. Recycled alumina can be used for rough cutting operation.